Kampung Ramadhan sebagai Upaya Penguatan Kesehatan Mental, Sosial, dan Spiritualitas Masyarakat melalui Talkshow, Zakat, dan Ibadah - Raisa Berlian; Santoso Santoso; Wahyi Busyro; Deprizon Deprizon; Dwita Razkia; Rika Septianingsih (Indonesian Scientific Journal, 2025)
Ramadan is a holy and blessed month for Muslims. During this month, Muslims are obligated to fast from dawn until sunset. In addition, Ramadan provides an opportunity for Muslims to strengthen their faith and piety as well as to enhance social bonds with others. In an effort to enhance faith, piety, and social connectedness, we took the initiative to organize the “Kampung Ramadan” (Ramadan Village) program. Community service activities are an integral part of the Tri Dharma of Higher Education, which demands the active contribution of academic institutions in addressing real-world social issues. Kampung Ramadan, initiated by the Faculty of Islamic Studies at Universitas Muhammadiyah Riau, is a concrete form of spiritually and socially based service during the holy month. Through an interdisciplinary approach presented in a talk show entitled